2008
DOI: 10.1016/j.tetlet.2008.01.132
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a pH-independent bifurcated amphiphile

Abstract: An efficient synthetic method for preparing bifurcated amphiphiles has been developed such that the functionality for attachment is located at the interface between the lipophilic and hydrophilic side chains. Attachment of the amphiphile to the repeat units of polymeric substrates enables the rapid preparation of amphiphilic homopolymers. Keywordsamphiphile; amphiphilic monomer; amphiphilic polymer; amphiphilic homopolymerThe human production and use of amphiphilic compounds dates to prehistory, when triacylgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Bifurcated amphiphile precursors 10-12 has also been previously described by our labs. 31 General procedure for encapsulation studies Amphiphilic homopolymer was dissolved into a non-polar solvent (toluene) at a range of concentrations with a final volume of 2 mL. Excess dye/guest ($0.010 g) was added and the vial sealed with parafilm.…”
Section: Experimental Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bifurcated amphiphile precursors 10-12 has also been previously described by our labs. 31 General procedure for encapsulation studies Amphiphilic homopolymer was dissolved into a non-polar solvent (toluene) at a range of concentrations with a final volume of 2 mL. Excess dye/guest ($0.010 g) was added and the vial sealed with parafilm.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Towards this end, our labs have reported a modular synthetic route towards the preparation of bifurcated amphiphilic units which are both neutral and independent of pH. 31 The synthesis involves the successive attachment of a long alkane chain (in this case dodecane) and an oligoethylene glycol chain (in this case tetra(ethylene glycol)) to a tris-alcohol core to provide amphiphilic unit 1. This novel bifurcated amphiphile can be easily synthesized in five steps with an overall 76% yield.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3a illustrates the anti-fog behavior of the copolymer films and a video is presented in the Supporting Information (Movie S1). It can be clearly observed that no fog forms on the surfaces of PDMAEMA 50 -b-FA 5 , PDMAEMA 50 -b-FA 11 , and P(DMAEMA 197 -co-FA 10 ), but for P(DMAEMA 150 -co-FA 24 ), a thick fog develops on the surface. The results indicate that the surface of the block copolymers has excellent anti-fog properties, but the surface of the random copolymer can prevent fogging only when it has a low FA content.…”
Section: Resultsmentioning
confidence: 98%
“…[10] 1,1,1-tris(hydroxymethyl)ethane, [11] 1,3,5-trisubstituted benzenes, [12] tertiary amines, [13] etc. Herein, we selected epichlorohydrin as the linking reagent for the preparation of the amphiphilic monomer because of its advantages such as simplifying the synthetic procedure, commercial availability, and low cost.…”
Section: Resultsmentioning
confidence: 99%